2017
DOI: 10.1021/acs.jproteome.7b00585
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin Conjugation Probed by Inflammation in Myeloid-Derived Suppressor Cell Extracellular Vesicles

Abstract: Ubiquitinated proteins carried by the extracellular vesicles (EV) released by myeloid-derived suppressor cells (MDSC) have been investigated using proteomic strategies to examine the effect of tumor-associated inflammation. EV were collected from MDSC directly following isolation from tumor-bearing mice with low and high inflammation. Among the 1092 proteins (high inflammation) and 925 proteins (low inflammation) identified, more than 50% were observed as ubiquitinated proteoforms. More than three ubiquitin-at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 52 publications
(145 reference statements)
3
21
0
Order By: Relevance
“…The MDSC chemotactics S100A8 and S100A9 are abundant in MDSC EVs and polarize macrophages into M2 phenotype (79). These pro-inflammatory proteins are characterized by multiple ubiquitination sites, and MDSC EVs were identified as carriers of enzymes catalyzing ubiquitination (80). Interestingly, EVs from TME-resident MDSC display a stronger immunosuppressive potential than those deriving from spleen or bone marrow MDSCs, suggesting the existence of different phenotypes and functions (81).…”
Section: Evs As Mir Shuttles and Mdsc Modulatorsmentioning
confidence: 99%
“…The MDSC chemotactics S100A8 and S100A9 are abundant in MDSC EVs and polarize macrophages into M2 phenotype (79). These pro-inflammatory proteins are characterized by multiple ubiquitination sites, and MDSC EVs were identified as carriers of enzymes catalyzing ubiquitination (80). Interestingly, EVs from TME-resident MDSC display a stronger immunosuppressive potential than those deriving from spleen or bone marrow MDSCs, suggesting the existence of different phenotypes and functions (81).…”
Section: Evs As Mir Shuttles and Mdsc Modulatorsmentioning
confidence: 99%
“…Recently, one of the areas of research in the immuno-oncology field has been focused on pharmacological inhibition of MDSC activity and combining these drugs with other known immunotherapeutic agents to improve therapeutic responses in cancer patients. A recent report suggested that common exosomal proteins (e.g., annexins, tetraspanins, cytoskeletal proteins, heat shock proteins) as well as several unique proteins are present in both MDSCs and MDSC-derived sEVs ( 143 , 144 ). These sEV-derived immune suppressive proteins participate in immune regulation in cancer-bearing hosts ( 143 , 144 ).…”
Section: Immunosuppressive Effects Of Immune Cell-derived Sevs In Canmentioning
confidence: 99%
“…Cancer cells secreted EVs, which were involved in the intercellular transfer of proteins, lipids, and genetic material (such as miRNAs). Those tumor-associated EVs represented an ideal candidate due to their ability to recirculate in body fluids during the process of MDSC generation from bone marrow in tumor microenvironment 29-31. In melanoma patients, some miRNAs (such as miR-99b, miR-100, miR-125a/-125b, miR-146a/-146b, miR-155, let-7e), which were highly detected in plasma as associated with EVs, mediated the generation and functional features of tumor M-MDSCs 8, 32, 33.…”
Section: Micrornas Regulate the Differentiation And Activation Of Tummentioning
confidence: 99%